1997
DOI: 10.1029/96jd03324
|View full text |Cite
|
Sign up to set email alerts
|

1993 Tropospheric OH Photochemistry Experiment: A summary and perspective

Abstract: Abstract. The 1993 OH Tropospheric Photochemistry Experiment was performed in the forested Colorado mountains during late summer and early fall 1993. Measurements of the OH radical were made by four different techniques; one pair provided an extensive intercomparison data set. A large number of other species that control OH and HO2 concentrations were also determined. These ancillary variables have been useful both in understanding intercomparison issues and in testing detailed model predictions of OH photoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…(1) Recent tropospheric field measurements have shown that there is still a significant disagreement between measured OH concentrations and the predictions from regional scale models [Crosley, 1997;McKeen et al, 1997]. Isoprene can be a major OH sink under certain conditions accounting for up to 30% of the OH removal rate [Biesenthal and Bottenheim, 1998 …”
Section: Oh + Csi-ia --• Productsmentioning
confidence: 99%
“…(1) Recent tropospheric field measurements have shown that there is still a significant disagreement between measured OH concentrations and the predictions from regional scale models [Crosley, 1997;McKeen et al, 1997]. Isoprene can be a major OH sink under certain conditions accounting for up to 30% of the OH removal rate [Biesenthal and Bottenheim, 1998 …”
Section: Oh + Csi-ia --• Productsmentioning
confidence: 99%
“…Today at least four radical species have been found to be important in the boundary layer: OH, NO 3 , O 3 , and, in certain environments, reactive halogen species [e.g., Atkinson, 2000;Crosley, 1997;Finlayson-Pitts and Pitts, 2000;Lelieveld and Dentener, 2000;Platt et al, 2002;Wayne et al, 1995]. For many years, a clear distinction was made between daytime ''photo chemistry'', with OH being the key radical, and nighttime radical chemistry, which is controlled by NO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…For many years, a clear distinction was made between daytime ''photo chemistry'', with OH being the key radical, and nighttime radical chemistry, which is controlled by NO 3 . Consequently, OH was neglected during the night and NO 3 during the day [e.g., Armerding et al, 1997;Atkinson, 2000;Crosley, 1997;Eisele et al, 1997;Finlayson-Pitts and Pitts, 2000;Fuentes et al, 2000;Kleinman, 2000;Logan et al, 1981;Monks et al, 1998;Platt, 1991;Wayne et al, 1991;Weaver et al, 1996]. In fact, OH and NO 3 measurements were often paused during nighttime and daytime, respectively [e.g., Allan et al, 1999;Brune et al, 1995;Geyer et al, 2001a;Hard et al, 1995;Heintz et al, 1996;Holland et al, 1998;Mount et al, 1997;Platt et al, 1981].…”
Section: Introductionmentioning
confidence: 99%
“…While its ambient concentration is low (typically <0.3 pptv), its high reactivity makes it the most important tropospheric cleansing agent, responsible for the removal of CH4 and numerous non-methane hydrocarbons [Crosley, 1997]. Through reactions with NO2, 802, and DMS, it is responsible for the production of HNO3 and H2SO4, compounds that are present in acid precipitation and are significant in the formation and growth of aerosols [Calvert et al, 1985].…”
Section: Introductionmentioning
confidence: 99%